Planning and Evaluating Geography Lessons with the National Standards for Education - Hoffmann, Karl Walter (Journal of Geography Education, 2009)
The demand for competence related assignments in geography lessons that are based on standards even increases the effort that has to be put into the didactic analysis when considering the following questions: How can spatial concepts and competences be connected? How can isolated knowledge be transferred into skills and how can the subject matters to be dealt with are combined to develop not only geographical but also interdisciplinary competences? What type and quality should the assignments correspond to?